CMOS-MEMS Vibro-Impact Devices and Applications - Tsai, Chun-Pu; Li, Wei-Chang (Frontiers in Mechanical Engineering, 2022)
CMOS-MEMS based vibro-impact devices that utilize impact induced nonlinear dynamics have been shown to yield unique and unprecedented functionalities with on-chip integration capability. For example, a 0.35-µm CMOS based capacitively transduced comb-driven folded-beam resonant switch has been integrated with backend circuits to demonstrate a zero-quiescent power wireless receiver operating at the low frequency (LF) band. In addition, CMOS-MEMS vibro-impact resonators have been used as AFM-alike surface condition monitoring for detecting chemical coating on structural sidewalls as well as clock generators with controllable duty cycles by manipulating the actuation conditions. This paper will review these achievements and discuss the limitations and challenges in developing the vibro-impact devices using CMOS-MEMS technology.